ASPEK EKONOMI PENGUSAHAAN TAMAN BURU MASIGIT KAREUMBI KABUPATEN SUMEDANG JAWA BARAT (The Economic Aspect of the Exertion Masigit Kareumbi Hunting Park in the Regency of Sumedang West Java) - A. Hernadi; Yanto Santosa; . Bahruni; Unu Nitibaskara (Department of Forest Resources Conservation and Ecotourism - IPB University, 2006)
Masigit Kareumbi Hunting Park (MKHP) as one of the 14 hunting parks exist in Indonesia has a prospective future. The potency of biophysic area which cover the area, accessibility, topography and vegetation condition can prospectively be exerted. In the other side, there is a tendency to exert hunting sport either for domestic hunters or foreigen hunters is a good chance for MKHP improvement. This research is aimed at analyzing economic prospect of MKHP exertion through the calculation of Net Present Value (NPV), Benefits Cost Ratio (BCR) and Internal Rate of Return (IRR). MKHP area has a natural power of attraction like flora, fauna, ecosystem or natural phenomenon to be developed through hunting activity, natural tourism, cultures, research, science and embrio supply for cultivation. Based on the analisys, the main activity for improving MKHP is by setting the plan, enclave relocation, infra structure establishment and the other things which support it. Besides to fulfill the conservation function, the preservation of habitat and population must be greatly paid attention. Two options are done to analyze this, that is through (1) exerting MKHP in the aspect of hunting and ecotourism, and (2) exerting MKHP in the aspect special hunting. The financial analysis shows that the MKHP exertion with the price 1.500 and 750 for deer and 150 and 100 for pig (trophy and non trophy) in the rate of 9% from hunting and ecotourism it gains NPV Rp 50.160.631.000,00 and BCR 1,677 (with breeding). But the exertion without breeding it gains NPV Rp 24.955.315.000,00 and BCR 1,476. The exertion through both scenarios is reasonable to do. The exertion from special hunting with breeding scenario is obtained NPV Rp 36.896.371.000,00 and BCR 1,548. The MKHP exertion through the special hunting without breeding result NPV Rp 19.2933690.000,00 and BCR 1,386. This means the exertion is acceptable.Keyword : Activity development, cost, benefits, opportunity, resources potency